2004
DOI: 10.1002/cncr.20286
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal/multicentric breast carcinoma

Abstract: To specifically investigate the effect that large‐vessel disease may have on cortical reorganization, we used functional magnetic resonance imaging to study patients with unilateral hemispheric hypoperfusion and impaired vasomotor reactivity from critical internal carotid or middle cerebral artery disease but without stroke. We hypothesized that when these patients used the hand contralateral to the hypoperfused hemisphere they would show unique activation in motor‐related areas of the normally perfused hemisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…These findings are consistent with several studies [24][25][26][27][28]. To our knowledge, however, no other study to date has examined the overall survival as well as the relapse-free survival.…”
Section: Distant Metastasessupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are consistent with several studies [24][25][26][27][28]. To our knowledge, however, no other study to date has examined the overall survival as well as the relapse-free survival.…”
Section: Distant Metastasessupporting
confidence: 94%
“…Many studies point out an increased risk for metastatic dissemination and, therefore, poorer outcome, a finding that is not currently reflected in the TNM classification [23][24][25][26][27]. As mentioned above, the prognostic relevance of the T category is a constant factor in regard to current and past classification [4] and survival of patients with breast cancer depends on several prognostic factors.…”
Section: Distant Metastasesmentioning
confidence: 95%
See 1 more Smart Citation
“…The current standard for staging MF/MC breast cancers is using the largest tumor diameter for T‐staging although it is unclear whether the current staging accurately predicts LN involvement. Multiple studies have demonstrated that aggregation of tumor foci may result in better prediction of nodal disease . On the other hand, a recent study by Duraker and Caynak found no difference in the incidence of node positivity when staging by aggregated tumor size versus largest tumor dimension in patients with MF/MC breast cancers .…”
Section: Discussionmentioning
confidence: 95%
“…Data on MF MC breast cancer as a risk factor for increased LR after BCT or MX are limited. The incidence of MF or MC breast cancer ranges from 4% to 65% between studies, partly attributable to differences in definitions (2,92). Approximately 30–63% of patients, clinically and mammographically suspected of unifocal disease, are found to have additional foci on serial sectioning of the MX specimen, approximately 80% of which lie outside the index quadrant (4,5,93–95).…”
Section: Discussionmentioning
confidence: 99%